Rational Structural Synthesis of Schemes of Crank-Slider Mechanisms of Gripping Devices - Pohrebniak, R. P. (Science and Transport Progress, 2025)
Purpose. The study is devoted to the determination of harmful redundant connections (RC) in the internal and external circuits of grippers based on paired schemes of crank-slider mechanisms. Methodology. The determination of redundant (repeated) connections was carried out using the universal structural theory of mechanisms. Findings. Mechanisms without redundant links, including gripper mechanisms, are more reliable, have a higher efficiency in operation, and are statically determined. Rational design of such mechanisms without a thorough structural analysis is difficult. In gripping devices, the determination of redundant connections in the contours of the mechanisms occurs at two different stages of their functioning: before clamping the object of manipulation and after. Such mechanisms of variable structure require an appropriate double structural analysis, the main purpose of which is to determine the repetitive connections at each of these stages. This structural analysis allowed us to determine the number and location of internal and external redundant links. The search for redundant bonds at the second stage of gripper operation, when new circuits in the mechanisms are formed, requires the use of an external structural formula. The elimination of redundant links in the internal contours of the mechanisms was accomplished by lowering the class of kinematic pairs. Reliable determination of the number of redundant links in the external circuits is possible only taking into account the fineness of the non-holding links. Originality. For the first time, a structural analysis of paired parallel-frame schemes of grippers based on the central and desaxial crank-slider mechanisms and having a variable structure with external one-sided non-retaining ties was performed. Practical value. The obtained research results made it possible to determine the location of internal and external redundant bonds in the contours of the mechanisms and to propose actions to reduce the number of harmful redundant bonds in the external contour of the mechanisms. The elimination of frictional excessive connections in the outer contour of the mechanisms by changing the shapes of the contacting surfaces of the clamping elements of the gripper was carried out.